Anteseden keberlanjutan usaha balai ekonomi desa (BALKONDES) - Intan Khamilatul Khasanah; Nur Laila Yuliani; Barkah Susanto; Pranita Siska Utami; Ravindra Ardiana Darmadi (LPMP Imperium, 2025)
Business sustainability in village economic centers (Balkondes) is crucial for enhancing the village economy and improving the welfare of local communities. This study analyzes the key factors influencing Balkondes businesses sustainability, focusing on three leading indicators: income generation, budget efficiency, and social impact. The research employs a quantitative approach, utilizing survey techniques to gather data from Balkondes managers and relevant stakeholders. The findings indicate that income generation significantly contributes to business sustainability by enabling optimal resource allocation and strengthening financial aspects. However, budget efficiency and social impact do not directly influence business sustainability. Public interest statements The findings of this research benefit Balkondes stakeholders and SOEs by helping them develop more effective and sustainable strategies. Consequently, this research can assist BUMN in achieving social and economic objectives while enhancing the sustainability of its businesses